Genetic diversity, drug resistance, and transmission patterns of tuberculosis based on whole-genome sequencing in Almaty, Kazakhstan - Takenov, Nurlan; Kaziyev, Alibi; Mukhamadi, Asfendiyar; Chingissova, Lyailya; Toxanbayeva, Bekzat; Bismilda, Venera; Adenov, Malik; Eralieva, Lyazzat; Nakisbekov, Narymzhan; Zhunussova, Gulnur (Frontiers in Microbiology, 2025)
Tuberculosis, particularly multidrug-resistant TB (MDR-TB), remains a major public health concern in Kazakhstan, where 26% of new TB cases are MDR, far exceeding the global average. To better understand the genetic diversity, drug resistance, and transmission dynamics of Mycobacterium tuberculosis in Kazakhstan, we conducted a retrospective study at the National Scientific Center of Phthisiopulmonology in Almaty from 2023 to 2024. Whole-genome sequencing (WGS) was performed on 272 culture-confirmed TB isolates collected from patients across the country. Phylogenetic analysis revealed the predominance of Lineage 2 (East Asian genotype, 72.4%) and Lineage 4 (Euro-American genotype, 26.8%). Drug resistance profiling identified 29.0% of isolates as MDR-TB, of which 3.3% were classified as pre-XDR and 0.7% as XDR. The most frequently observed resistance-associated mutations were katG S315T (99.2%) and rpoB S450L (91.1%). Cluster analysis using a ≤ 12 SNP threshold identified 22 genomic clusters involving 80 isolates (29.4%), indicating recent and possibly ongoing transmission. Spatial mapping showed that nearly 60% of clusters spanned multiple regions, while others were highly localized, suggesting household or close-contact transmission. A Mantel correlogram test revealed a statistically significant correlation between geographic and genomic SNP distances in Almaty and Almaty Region (r = 0.0634, p = 0.041) within the first distance class (average 5 km, range 0–8 km). These findings suggest that patients living in close proximity are more likely to carry genetically similar strains. As distance increases, geographic proximity becomes less predictive of transmission, with other factors—such as mobility, shared environments, or healthcare contact—likely playing a greater role. Our findings underscore the need to integrate WGS into national TB control programs to guide targeted interventions, enhance surveillance, and curb the spread of drug-resistant TB strains across Kazakhstan.